EFFECTS OF SPECIMEN VOLUME AND TEMPERATURE ON MEASUREMENTS OF SHORE HARDNESS - Altındag R. (My University, 2002)
In this study, the effect of specimen size, temperature and water content on Shore hardness is investigated. With this objective, core samples of different sizes were prepared from nine different types of rocks. Firstly, Shore hardness (SH) tests on these samples were conducted and hardness values were determined using Shore scleroscope apparatus. Secondly, the same specimens were conditioned in a drying-out cupboard at different temperatures. Then, the Shore hardness values of the saturated specimens were obtained according to specimen volume. In order to determine die SH values of the rocks, the minimum test specimen volume required is suggested.